Baicalin Mitigates the Neuroinflammation through the TLR4/MyD88/NF-κB and MAPK Pathways in LPS-Stimulated BV-2 Microglia. (9th November 2022) - Li, Baojing; Wang, Mingming; Chen, Shuai; Li, Manping; Zeng, Jing; Wu, Saichun; Tu, Yuanqing; Li, Yanping; Zhang, Rongping; Huang, Feng; Tong, Xiaoyun
Abstract : Baicalin (BA) is a major flavone from Scutellaria baicalensis Georgi and has showed significant curative effects in Parkinson's and Alzheimer's diseases. In the present study, we investigated the effects of BA on antineuroinflammation and related signaling cascade in lipopolysaccharide- (LPS-) induced BV-2 microglial model. The results showed that BA significantly attenuated inflammatory mediators (NO, iNOS, IL-1 β, COX-2, and PGE2) and suppressed the expression of miR-155. More crucially, BA could regulate the expression of related proteins in Toll-like receptor 4 (TLR4)/myeloid differentiation protein 88 (MyD88)/nuclear factor κ B (NF- κ B) pathway and suppress the phosphorylation of mitogen-activated protein kinase (MAPK) family. In addition, molecular docking analysis indicated that BA binds to the amino acids Lie 63 and Tyr 65 of TLR4 by π -σ and π -π T-shaped interaction. Thus, BA suppressed the LPS-stimulated neuroinflammation in BV-2 microglia by blocking the TLR4-mediated signal transduction through TLR4/MyD88/NF- κ B and MAPK pathways and inhibiting the miR-155 expression. Our findings demonstrated that BA could be a valuable therapeutic for the treatment of neuroinflammation and neurodegenerative diseases.